A hexasaccharide from capsular polysaccharide of carbapenem-resistant Klebsiella pneumoniae KN2 is a ligand of Toll-like receptor 4. (15th February 2022) - Lee, I-Ming; Huang, Tzu-Yin; Yang, Feng-Ling; Johansson, Victor; Hsu, Chun-Ru; Hsieh, Pei-Fang; Chen, Shin-Tai; Yang, Yen-Ju; Konradsson, Peter; Sheu, Jyh-Horng; Wang, Jin-Town; Wu, Shih-Hsiung
Abstract: Klebsiella pneumoniae serotype KN2 is a carbapenem-resistant strain and leads to the health care-associated infections, such as bloodstream infections. Its capsular polysaccharide (CPS) was isolated and cleaved by a specific enzyme from a bacteriophage into a hexasaccharide-repeating unit. With GC–MS, NMR, and Mass analyses, the structure of KN2 CPS was determined to be {→3)- β -D-Glc p -(1→3)-[ α -D-Glc p A-(1→4)- β -D-Glc p -(1→6)]- α -D-Gal p -(1→6)- β -D-Gal p -(1→3)- β -D-Gal p -(1→}n . We demonstrated that 1 μg/mL CPS could stimulate J774A.1 murine macrophages to release tumor necrosis factor- α (TNF- α ) and interleukin-6 (IL-6) in vitro. Also, we proved that KN2 CPS induced the immune response through Toll-like receptor 4 (TLR4) in the human embryonic kidney (HEK)-293 cells. Strikingly, the hexasaccharide alone shows the same immune response as the CPS, suggesting that the hexasaccharide can shape the adaptive immunity to be a potential vaccine adjuvant. The glucuronic acid (GlcA) on other polysaccharides can affect the immune response, but the GlcA-reduced KN2 CPS and hexasaccharide still maintain their immunomodulatory activities.